EVALUATION OF THE SISTER APPLICATION IMPLEMENTATION IN SUPPORTING THE ACADEMIC PERFORMANCE OF LECTURERS AT IAI AL-HIDAYAH BOGOR - Muharam, Aditya; Sarifudin, Sarifudin; Ubaedillah, Ahmad (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2026)
The Integrated Resource Information System (SISTER) is an application developed by the Ministry of Education, Culture, Research, and Technology to support integrated lecturer data governance across all higher education institutions in Indonesia. This study aims to evaluate the implementation of the SISTER application in supporting lecturers’ academic performance, particularly in terms of managing data on the tridharma of higher education, such as education, research, and community service carried out by lecturers at IAI Al-Hidayah Bogor. The method used is a qualitative descriptive case study at IAI Al-Hidayah, Bogor. Data were collected through interviews, observations, and questionnaires with lecturers who use the SISTER application at IAI Al-Hidayah Bogor. The evaluation results show that in general, SISTER provides convenience in recording and reporting academic activities, but there are still several obstacles such as a suboptimal user interface, imperfect data integration, and the need for further training for lecturers. These findings underscore the importance of continuously improving the SISTER application to better support lecturers' academic performance and enhance higher education governance in Indonesia.